2020
DOI: 10.1002/ghg.2021
|View full text |Cite
|
Sign up to set email alerts
|

Coupled CO2 capture and thermochemical heat storage of CaO derived from calcium acetate

Abstract: CaO/Ca(OH) 2 thermochemical heat storage (THS) technology is considered to be one of the most promising technologies for large-scale solar energy storage. However, the THS performance of raw CaO-based materials decreases during multiple cycles. In this work, CaO derived from calcium acetate (Ac-CaO) is prepared and applied to a coupled system that achieved simultaneous CaO/Ca(OH) 2 THS and CO 2 capture. The CO 2 capture and THS performances of Ac-CaO are always higher than those of calcined limestone owing to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 39 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Acetic acid (AA) is commonly used as a modifier of limestone. The carbonation conversion of modified acetic acid is 2.33 higher than unmodified calcined limestone [ 108 ] and higher than other organic acids during the initial cycle [ 109 ]. This characteristic contributes to a high porous surface and small grain size due to the decomposition of calcium acetate into acetone, CO 2 and CaO [ 108 ].…”
Section: Improvement Of Sorbentmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetic acid (AA) is commonly used as a modifier of limestone. The carbonation conversion of modified acetic acid is 2.33 higher than unmodified calcined limestone [ 108 ] and higher than other organic acids during the initial cycle [ 109 ]. This characteristic contributes to a high porous surface and small grain size due to the decomposition of calcium acetate into acetone, CO 2 and CaO [ 108 ].…”
Section: Improvement Of Sorbentmentioning
confidence: 99%
“…The carbonation conversion of modified acetic acid is 2.33 higher than unmodified calcined limestone [ 108 ] and higher than other organic acids during the initial cycle [ 109 ]. This characteristic contributes to a high porous surface and small grain size due to the decomposition of calcium acetate into acetone, CO 2 and CaO [ 108 ]. Moreover, modified limestone with AA as sorbent can reduce the energy penalty when integrating with a power plant.…”
Section: Improvement Of Sorbentmentioning
confidence: 99%
“…These results proved that calcium-based materials with acetic acid addition have richer pore structures, larger specific surface area, and pore volume compared with no acetic acid addition. 37 Sun et al 38 found that the energy storage performance of CaO prepared from calcium acetate was always higher than that of CaO prepared from limestone. Li et al 39 prepared CaO by using the thermal decomposition of calcium acetate to obtain higher CaO conversion.…”
Section: Introductionmentioning
confidence: 99%